Freehand architectural drawing and painting in the context of design of single-family houses. Theory and practice of teaching - Chęć-Małyszek, Agnieszka; Małys, Dominika (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
This article is devoted to the process of education in the field of freehand drawing and painting and how the acquired skills are used by students in the design process at a later stage of study. The publication draws attention to the essence of drawing and painting in the design process. The aim of the work is to analyze the teaching method in the subject of Freehand drawing, graphics and painting and Designing single-family houses. It was shown how the acquired skills and knowledge in the field of art in one subject taught in the first year of Architecture are used during the implementation of design tasks in the second subject. The author presents her own experience in teaching freehand drawing students of Architecture, Lublin University of Technology. The article uses the method of observation, an analysis of students’ works and an interview was conducted. The presented research has shown that the skillful use of drawing and painting techniques as well as basic knowledge of art is essential in the processes of creative architectural design, especially when the idea of ​​the idea is not sufficient to solve the design problem.